Negative electrode active material for lithium-ion secondary batteries, method of manufacturing the same, and negative electrode for lithium-ion secondary batteries
Patent Information
- Application Number
- KR1020247031248
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-03-03
- Filing Date
- 2023-01-17
- Publication Date
- 2026-10-21
- Estimated Expiration
- 2043-01-17
Smart Images

Figure 112024102222290-PCT00017_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a negative electrode active material for a lithium-ion secondary battery, a method for manufacturing the same, and a negative electrode for a lithium-ion secondary battery. More specifically, the invention relates to a negative electrode active material for a lithium-ion secondary battery with excellent cycle characteristics in which silicon particles are dispersed in a lithium aluminosilicate forming a three-dimensional network structure, a method for manufacturing the same, and a negative electrode for a lithium-ion secondary battery. Background Technology
[0002] Secondary batteries have come to be widely used in, for example, mobile phones, personal computers, power tools, hybrid electric vehicles (HEVs), and electric vehicles (PEVs). In particular, lithium-ion batteries have high power output and high energy density, so they are widely used as batteries for portable devices and automotive batteries. Graphite materials are mainly used as the negative electrode active material for lithium-ion batteries. Although the negative electrode of a lithium-ion battery using graphite as the negative electrode active material has good cycle characteristics, its charge capacity is relatively small, at about 372 (mA·h / g).
[0003] Recently, as the demand for lithium-ion batteries as automotive batteries has increased, there is a desire for further high energy density in lithium-ion batteries. To improve the energy density of lithium-ion batteries, it is necessary to increase the charge capacity through the negative electrode active material included in the negative electrode of the lithium-ion battery. In this regard, silicon-based negative electrodes using silicon material as the negative electrode active material, which has a charge capacity of 4200 (mA·h / g) that is more than 10 times that of graphite material, are attracting attention, and active research and development is being carried out.
[0004] Silicon-based negative electrodes currently in commercial use include Si negative electrodes composed solely of pure silicon and SiO negative electrodes composed of SiO, which is a mixture of Si and SiO2. Here, the SiO negative electrode has a structure in which silicon is dispersed within silicon oxide. Since the silicon oxide suppresses the expansion and contraction of silicon, the SiO negative electrode exhibits superior cycle characteristics compared to Si negative electrodes composed solely of silicon. However, during the initial charge, the silicon oxide of the SiO negative electrode reacts with lithium to form Li4SiO4, which reduces Coulomb efficiency. For this reason, development is also underway for Li-Si-O negative electrodes in which lithium is pre-doped into the SiO negative electrode. However, technical challenges remain because the cycle characteristics of Li-Si-O negative electrodes are inferior to those of graphite-based negative electrodes.
[0005] Patent Document 1 discloses a silicon-silicon oxide-lithium-based composite that is useful as a negative electrode active material for a lithium-ion secondary battery, a method for manufacturing the same, and a negative electrode material for a non-aqueous electrolyte secondary battery using the powder thereof. The negative electrode active material for a lithium-ion secondary battery disclosed in Patent Document 1 has a structure in which silicon is dispersed in silicon oxide, and lithium is doped into the silicon oxide.
[0006] Patent Document 2 discloses a negative electrode for a lithium-ion secondary battery. The negative electrode for a lithium-ion secondary battery described in Patent Document 2 comprises SiO2 and LiAlO2, and comprises Li4SiO4 and Al formed after initial lithium charging.
[0007] Patent Document 3 discloses a negative electrode active material for a non-aqueous electrolyte secondary battery comprising a lithium silicate composite particle comprising a lithium silicate phase and silicon particles dispersed within the lithium silicate phase. It is described that the lithium silicate phase included in the lithium silicate composite particle of the negative electrode active material for a non-aqueous electrolyte secondary battery disclosed in Patent Document 3 is an oxide phase comprising Li, Si, O, and M (M is an element excluding Group 1 of alkali metals, Group 16 of oxygen groups, Group 18 of noble gases, and Si). Prior art literature
[0008] Japanese Published Patent Application No. 2007-294423, Japanese Published Patent Application No. 2013-197012, International Publication No. 2019 / 130787
[0009] Inorg. Mater., 1987, 23, 1835-1837, Atdaev BS, Grin'VF, Sal'kov EA, Chalaya.VGRuss. J. Inorg. Chem., 1986, 31, 503-506, Kosorukov AA, Nadel LG, Chirkov AS. The problem to be solved
[0010] However, the above-mentioned prior art has the following problems. The silicon-silicon oxide-lithium-based composite disclosed in Patent Document 1, which is useful as a negative electrode active material for a lithium-ion secondary battery, has a structure in which silicon is dispersed in silicon oxide, but the components in the silicon oxide are Li, Si, and O, and Al is not included as a component. For this reason, the silicon oxide is not a Li-Al-Si-O-based compound.
[0011] In addition, the negative electrode for a lithium-ion secondary battery disclosed in Patent Document 2 includes SiO2 and LiAlO2, and thus the negative electrode includes Al as a negative electrode active material. However, the negative electrode merely includes SiO2 and LiAlO2 as respective components and does not include a Li-Al-Si-O system compound. Furthermore, the negative electrode for a lithium-ion secondary battery includes Li4SiO4 and Al as Li4SiO4 is formed after initial lithium charging.
[0012] In addition, the lithium silicate phase included in the lithium silicate composite particles of the negative electrode active material for a non-aqueous electrolyte secondary battery disclosed in Patent Document 3 comprises Li, Si, O, and M defined as a wide range of elements (M is an element excluding Group 1 of alkali metals, Group 16 of oxygen groups, Group 18 of noble gases, and Si), and is not designed with a composition targeting a specific compound having a three-dimensional network structure. In this regard, the three-dimensional network structure cannot be the main phase of the matrix.
[0013] As such, the negative electrode active materials for lithium-ion secondary batteries disclosed in Patent Documents 1 to 3 do not all have a Li-Al-Si-O-based compound having a three-dimensional network structure as the main component. Consequently, in the negative electrode active materials for lithium-ion secondary batteries and negative electrode materials containing silicon particles disclosed in Patent Documents 1 to 3, the silicon particles collapse due to the expansion and contraction of the silicon particles accompanying the absorption and release of lithium. As a result, a lithium-ion secondary battery equipped with a negative electrode containing the negative electrode active materials disclosed in Patent Documents 1 to 3 has the problem that its charge / discharge capacity decreases with each repeated charge / discharge cycle, and the discharge capacity retention rate (cycle characteristics) decreases.
[0014] The present invention is made in consideration of the problems of these conventional technologies, and aims to provide a negative electrode active material for a lithium-ion secondary battery, a method for manufacturing the same, and a negative electrode for a lithium-ion secondary battery that suppresses the breakdown of silicon particles due to the expansion and contraction of silicon particles accompanying the absorption and release of lithium, and suppresses the decrease in discharge capacity retention rate (cycle characteristics) even when charging and discharging are repeated. means of solving the problem
[0015] The negative electrode active material for a lithium-ion secondary battery targeted by the present invention is a composite in which silicon particles are dispersed in a matrix having a lithium aluminosilicate having a three-dimensional network structure. In order to achieve the above objective, the present invention adopted a lithium aluminosilicate having a three-dimensional network structure represented by the following general formula (1) as a matrix for dispersing silicon particles included in the negative electrode active material for a lithium-ion secondary battery. By doing so, it was discovered that the discharge capacity characteristics and charge / discharge capacity retention rate of the negative electrode active material for a lithium-ion secondary battery could be balanced, and thus the present invention also possesses desirable cycle characteristics for a lithium-ion secondary battery for automotive applications.
[0016] That is, the present invention provides a negative electrode active material for a lithium-ion secondary battery, characterized in that, firstly, silicon particles are dispersed in a matrix having a lithium aluminosilicate having a three-dimensional network structure, and the lithium aluminosilicate is represented by the following general formula (1).
[0017] [Chemical Formula 1]
[0018]
[0019] Here, in the above general formula (1), x satisfies the conditions 0.4 ≤ x ≤ 2.5, y 0.4 ≤ y ≤ 6.8, and δ -0.4 ≤ δ ≤ 0.4.
[0020] In addition, the negative electrode active material for lithium-ion secondary batteries is,
[0021] (a) In the above general formula (1), the ratio of Si to Al (y / x) is in the range of 1.0 ≤ (y / x) ≤ 5.5,
[0022] (b) that the lithium aluminosilicate is at least one selected from LiAlSiO4, LiAlSi2O6 and LiAlSi3O8,
[0023] (c) The above lithium aluminosilicate, in the crystal structure analysis by X-ray diffraction as specified in JIS H7805:2005,
[0024] As diffraction peaks 2θ (deg) originating from silicon, 28.20–28.60, 47.10–47.50, 55.90–56.30, and,
[0025] Having diffraction peaks 2θ (deg) originating from lithium aluminosilicate, ranging from 25.10 to 25.90, 47.10 to 47.90, and 55.80 to 56.80,
[0026] (d) The content of the silicon particles included in the negative electrode active material for the lithium-ion secondary battery is 40 to 90 mass%,
[0027] (e) It is considered that the average particle size of the silicon particles is 5 to 100 nm, etc., as a preferred means.
[0028] The present invention, secondly, is a method for manufacturing a negative electrode active material for a lithium-ion secondary battery in which silicon particles are dispersed in a matrix comprising a lithium aluminosilicate having a three-dimensional network structure,
[0029] Process (I); a process for manufacturing lithium aluminosilicate having a three-dimensional network structure by mixing and grinding lithium carbonate, aluminum hydroxide, and silicon dioxide, and then calcining at a temperature of 800 to 1000 ℃ under an atmospheric pressure atmosphere, and
[0030] Process (II); a process for manufacturing a negative electrode active material precursor by mixing and grinding the lithium aluminosilicate and silicon particles manufactured in the above process (I), and
[0031] Process (III); comprising a process of sintering the negative electrode active material precursor prepared in Process (II) under an inert gas atmosphere,
[0032] The above lithium aluminosilicate is characterized by being represented by the following general formula (1).
[0033] [Chemical Formula 2]
[0034]
[0035] Here, in the above general formula (1), x satisfies the conditions 0.4 ≤ x ≤ 2.5, y 0.4 ≤ y ≤ 6.8, and δ -0.4 ≤ δ ≤ 0.4.
[0036] The present invention is, thirdly, a negative electrode for a lithium-ion secondary battery comprising the negative electrode active material for the lithium-ion secondary battery. Effects of the invention
[0037] The negative electrode active material for a lithium-ion secondary battery and the negative electrode for a secondary battery comprising the negative electrode active material for a lithium-ion secondary battery according to the present invention have excellent discharge capacity characteristics and discharge capacity retention rate (cycle characteristics). Therefore, according to the present invention, it is possible to make the lithium-ion secondary battery smaller and lighter, and by mounting the lithium-ion secondary battery in a mobile phone, personal computer, power tool, hybrid electric vehicle (HEV), or electric vehicle (PEV), it is possible to provide a product with high performance. Brief explanation of the drawing
[0038] Figure 1 is a model diagram showing the three-dimensional network structure of LiAlSiO4 constituting the negative electrode active material for a lithium-ion secondary battery of the present invention. FIG. 2 is a model diagram showing the three-dimensional network structure of LiAlSi2O6 constituting the negative electrode active material for a lithium-ion secondary battery of the present invention. FIG. 3 is a model diagram showing the three-dimensional network structure of LiAlSi3O8 constituting the negative electrode active material for a lithium-ion secondary battery of the present invention. FIG. 4 is a flowchart showing each process of the method for manufacturing a negative electrode active material for a lithium-ion secondary battery according to the present invention. Figure 5 is a graph showing the X-ray diffraction (XRD) measurement results of a composite (before charging and discharging the secondary battery) composed of LiAlSiO4 and Si (silicon particles) constituting the negative electrode active material for the lithium-ion secondary battery of the present invention. Figure 6 is a graph showing the X-ray diffraction (XRD) measurement results of a composite (after charging and discharging the secondary battery) composed of LiAlSiO4 and Si (silicon particles) constituting the negative electrode active material for the lithium-ion secondary battery of the present invention. Figure 7 shows the measurement results of the diffraction pattern by X-ray diffraction (XRD) of the lithium aluminosilicate prepared in Example 1, Figure 7(a) is the measured XRD profile of the lithium aluminosilicate prepared in Example 1, and Figure 7(b) shows the diffraction peaks of the known LiAlSiO4 as a reference XRD profile. FIG. 8 is a model diagram showing the structure of a secondary battery having a negative electrode comprising a negative electrode active material for a lithium-ion secondary battery according to the present invention. Figure 9 shows the measurement results of the diffraction pattern by X-ray diffraction (XRD) of the lithium aluminosilicate prepared in Comparative Example 1, Figure 9(a) is the measured XRD profile of the lithium aluminosilicate prepared in Comparative Example 1, and Figure 9(b) shows the diffraction peaks of the known Li2Si2O5 as a reference XRD profile. This is the measurement result of the diffraction pattern by X-ray diffraction (XRD) of the lithium aluminosilicate obtained in Comparative Example 1. FIG. 10 is a graph showing the relationship between the charge-discharge cycle and the discharge capacity retention rate (cycle characteristics) in a secondary battery equipped with a negative electrode comprising a negative electrode active material for a lithium-ion secondary battery according to the present invention. Specific details for implementing the invention
[0039] [First Embodiment]
[0040] A negative electrode active material for a lithium-ion secondary battery according to the first embodiment will be described. The negative electrode active material for a lithium-ion secondary battery according to the present embodiment is characterized by being a composite in which silicon particles are dispersed in a matrix having a lithium aluminosilicate having a three-dimensional network structure as the main phase. That is, the matrix constituting the negative electrode active material for a lithium-ion secondary battery according to the present embodiment has a lithium aluminosilicate having a three-dimensional network structure as the main phase. Here, "main phase" refers to a case where the lithium aluminosilicate having a three-dimensional network structure is contained in the matrix at a concentration of 50 mol% or more. Furthermore, "main phase" refers to a case where the matrix constituting the negative electrode active material for a lithium-ion secondary battery according to the present embodiment is composed solely of lithium aluminosilicate having a three-dimensional network structure, and the lithium aluminosilicate having a three-dimensional network structure may be contained in the matrix at a concentration of 100 mol%.
[0041] The lithium aluminosilicate having a three-dimensional network structure, which is the matrix constituting the negative electrode active material for the lithium-ion secondary battery of the present embodiment, is represented by the following general formula (1).
[0042] [Chemical Formula 3]
[0043]
[0044] Here, in the above general formula (1), x is 0.4 ≤ x ≤ 2.5, y is 0.4 ≤ y ≤ 6.8, δ represents oxygen non-determinacy, and satisfies the condition -0.4 ≤ δ ≤ 0.4. In the above general formula (1), x and y may each be independently the same or different. Furthermore, in the above general formula (1), if x is 0.5 or greater, it is preferable because sufficient Al-Si-O bonds can be formed from the perspective of forming a three-dimensional network structure. If x is 1.2 or less, lithium ions (Li + In terms of conductivity, Al is lithium ion (Li + It is desirable because it does not hinder the movement of ). In addition, if y is 0.5 or higher, it is desirable because sufficient Al-Si-O bonds can be formed from the perspective of forming a three-dimensional network structure. If y is 5.5 or lower, it is desirable because the formation of SiO2 that can react with lithium (Li) during charging and discharging can be suppressed from the perspective of initial efficiency. δ represents the non-oxygenation in the metal oxide, and if δ is -0.4 or higher and 0.0 or lower, it is a value that can exist as an oxygen deficiency accompanied by oxygen vacancies, and if δ is 0.0 or higher and 0.4 or lower, it is a value that can exist as an oxygen excess due to the introduction of interstitial oxygen or metal defects.
[0045] Figures 1 to 3 are model diagrams showing the microstructures of lithium aluminosilicate, which are negative electrode active material matrices for lithium-ion secondary batteries. Figure 1 is a model diagram showing the microstructure and structural formula of LiAlSiO4, Figure 2 is a model diagram showing the microstructure of LiAlSi2O6, and Figure 3 is a model diagram showing the microstructure of LiAlSi3O8. The lithium aluminosilicates shown in Figures 1 to 3 all have covalent bonds formed between the atoms of Al-Si-O, forming a network (three-dimensional network structure) between these atoms, and have a branched structure with a high proportion of covalent bonds. The three-dimensional network structure referred to here means a structure in which elements other than the mobile ion lithium are covalently bonded in three dimensions. Lithium ions can move freely within the Li-Al-Si-O compound during charge-discharge reactions. By bonding elements other than lithium to form a three-dimensional structure without interposing lithium, it is possible to achieve the effect of strength enhancement through the three-dimensional network structure of the lithium aluminosilicate while maintaining lithium ion conductivity. For example, LiAlSiO4, LiAlSi2O6, and LiAlSi3O8 can be used as a matrix for dispersing silicon particles included in the negative electrode active material for a lithium-ion secondary battery according to the present embodiment. Furthermore, among lithium aluminosilicates, LiAlSiO4 is particularly preferred from the perspective of stability and durability of the three-dimensional network structure. Additionally, as a matrix for dispersing silicon particles included in the negative electrode active material for a non-aqueous electrolyte lithium-ion secondary battery according to the present embodiment, a lithium metal silicate in which the aluminum constituting the lithium aluminosilicate is substituted with Ca, Mg, Ti, V, Fe, Ta, Y, Zr, Bi, Mn, Ba, etc., which have chemical properties similar to those of aluminum, can be used.
[0046] In the crystal structure analysis by X-ray diffraction (XRD) specified in JIS H7805:2005, the lithium aluminosilicate constituting the negative electrode active material for a lithium-ion secondary battery has 28.20 to 28.60, 47.10 to 47.50, and 55.90 to 56.30 as diffraction peaks originating from silicon, and 25.10 to 25.90, 47.10 to 47.90, and 55.80 to 56.80 as diffraction peaks originating from lithium aluminosilicate.
[0047] In the lithium aluminosilicate constituting the negative electrode active material for a lithium-ion secondary battery according to the present embodiment, it is preferable that the ratio (y / x) of Si (silicon) and Al (aluminum) constituting the lithium aluminosilicate in the above general formula (1) satisfies the condition 1.0 ≤ (y / x) ≤ 5.5. It is preferable that the Si / Al ratio (y / x), which is the ratio of Si (silicon) and Al (aluminum) constituting the lithium aluminosilicate, is within the above range because it forms a three-dimensional network structure without excess or deficiency. On the other hand, the disadvantages when the Si / Al ratio (y / x) is outside the above range are as follows. That is, when the Si / Al ratio (y / x) is less than 1.0, it is not desirable because Al2O3 appears as a secondary phase in addition to the main phase three-dimensional network structure matrix. In addition, when the Si / Al ratio (y / x) exceeds 5.5, it is undesirable because SiO2, which lowers initial efficiency, appears as a floating component in addition to the columnar three-dimensional network structure matrix.
[0048] In addition, the lithium aluminosilicate constituting the negative electrode active material for a lithium-ion secondary battery of the present embodiment can be the subject of the present invention even if the Si / Al ratio (y / x) is outside the above range, provided that it satisfies the above general formula (1). The reason is that although the above disadvantage occurs when the Si / Al ratio (y / x) is outside the above range, the main phase takes on a three-dimensional network structure, so the effect intended by the present invention can be expressed.
[0049] In this way, if the lithium aluminosilicate used as the main matrix of the silicon particles constituting the negative electrode active material for a lithium-ion secondary battery satisfies the above general formula (1), the electrical conductivity of the silicon particles in the negative electrode containing the negative electrode active material using the lithium aluminosilicate can be secured. Furthermore, if the lithium aluminosilicate satisfies the above general formula (1), the lithium aluminosilicate has high strength, and can maintain a three-dimensional network structure even after charging and discharging the lithium-ion secondary battery equipped with the negative electrode. For this reason, the expansion and contraction of the silicon particles, which are the active material included in the negative electrode active material for a lithium-ion secondary battery, are suppressed by the lithium aluminosilicate. As a result, the silicon particles, which are the active material included in the negative electrode active material for a lithium-ion secondary battery, do not collapse even after charging and discharging the lithium-ion secondary battery equipped with the negative electrode.
[0050] It is preferable that the average particle size of the silicon particles is 5 to 100 nm. It is preferable that the average particle size of the silicon particles be 5 nm or larger because the microstructure of the negative electrode active material for a lithium-ion secondary battery becomes stable. It is preferable that the average particle size of the silicon particles be 100 nm or smaller because the expansion of the silicon particles due to volume change during charging and discharging of a lithium-ion secondary battery equipped with a negative electrode using the negative electrode active material for a lithium-ion secondary battery of the present embodiment can be suppressed by the miniaturization of the silicon particles. In addition, the average particle size of the silicon particles can be calculated by the Sherrer equation from the full width at half maximum of the Si peak by performing XRD measurement of the negative electrode active material for a lithium-ion secondary battery of the present embodiment. Here, the Sherrer equation is expressed as D = Kλ / Bcosθ, where D is the crystal size (nm), K is the Sherrer constant, λ is the wavelength of the X-ray (nm), B is the full width at half maximum (rad), and θ is the Bragg angle (rad).
[0051] The content of silicon particles (Si particles) included in the negative electrode active material for a lithium-ion secondary battery according to the present embodiment is preferably 40 to 90 mass%. If the content of silicon particles is 40 mass% or more, it is preferable because the electrical conductivity of the silicon particles in the negative electrode comprising the negative electrode active material using silicon particles and lithium aluminosilicate as a matrix can be secured, and the charging and discharging of the lithium-ion secondary battery equipped with the negative electrode becomes possible. On the other hand, if the content of silicon particles is 90 mass% or less, it is preferable because the discharge capacity retention rate (cycle characteristics) of the lithium-ion secondary battery equipped with the negative electrode can be improved.
[0052] In summary, the negative electrode active material for a lithium-ion secondary battery according to the present embodiment is composed of lithium aluminosilicate capable of maintaining a three-dimensional network structure as a matrix of silicon particles, thereby suppressing the breakdown of silicon particles and providing a lithium-ion secondary battery with excellent discharge capacity retention rate (cycle characteristics).
[0053] [Second Embodiment]
[0054] Next, a method for manufacturing a negative electrode active material for a lithium-ion secondary battery according to the second embodiment will be described. FIG. 4 is a flowchart showing each process of the method for manufacturing a negative electrode active material for a lithium-ion secondary battery according to the present embodiment. As shown in FIG. 4, the method for manufacturing a negative electrode active material for a lithium-ion secondary battery according to the present embodiment is a method for manufacturing a negative electrode active material for a lithium-ion secondary battery in which silicon particles are dispersed in a matrix comprising a lithium aluminosilicate having a three-dimensional network structure, and comprises the following processes (I) to (III). Each process will be described below.
[0055] <Process (I); Process for manufacturing lithium aluminosilicate>
[0056] The method for manufacturing a negative electrode active material for a lithium-ion secondary battery according to the present embodiment includes process (I); and a process for manufacturing lithium aluminosilicate. The raw materials for the lithium aluminosilicate manufactured in process (I) are lithium carbonate, aluminum hydroxide, and silicon dioxide. These raw materials are weighed in a predetermined amount. The mixing ratio (mass ratio) of lithium carbonate, aluminum hydroxide, and silicon dioxide is not particularly limited as long as it is a mixing ratio capable of forming a lithium aluminosilicate having a three-dimensional network structure, but when producing LiAlSiO4, it is preferable that the mass ratio of lithium carbonate : aluminum hydroxide : silicon dioxide is 2.0 : 3.0 : 4.0. In addition, when producing LiAlSi2O6, the above-mentioned ratio of silicon dioxide can be doubled, and when producing LiAlSi3O8, the above-mentioned ratio of silicon dioxide can be tripled to synthesize it. Here, the mass ratio of lithium carbonate : aluminum hydroxide : silicon dioxide can be appropriately determined by the content of lithium, aluminum, and silicon contained in each raw material. In addition, in addition to lithium carbonate used as a raw material in process (I), lithium hydroxide, lithium oxide, and lithium sulfate may be used. In addition to aluminum hydroxide used as a raw material in process (I), aluminum oxide, aluminum carbonate, aluminum sulfate, etc. may be used.
[0057] Next, a predetermined amount of lithium carbonate, aluminum hydroxide, and silicon dioxide, which are the raw materials for lithium aluminosilicate, are mixed and ground. The mixing and grinding of these raw materials is carried out for a predetermined time using a device such as a ball mill. After mixing and grinding, the raw materials become a mixture of lithium carbonate, aluminum hydroxide, and silicon dioxide having a predetermined particle size.
[0058] In addition, the raw material obtained above is calcined at a temperature of 800 to 1000 ℃ under an atmospheric pressure atmosphere. It is preferable if the calcination temperature is 800 ℃ or higher, as this allows the reaction between aluminum hydroxide and silicon dioxide to proceed sufficiently, thereby forming covalent bonds between the atoms of Al-Si-O. It is preferable if the calcination temperature is 1000 ℃ or lower, as this allows the three-dimensional network structure of the lithium aluminosilicate to be maintained.
[0059] <Process (II); Process for manufacturing a negative electrode active material precursor>
[0060] The method for manufacturing a negative electrode active material for a lithium-ion secondary battery according to the present embodiment includes a process for manufacturing a negative electrode active material precursor by mixing and grinding the lithium aluminosilicate and silicon particles manufactured in process (I). The negative electrode active material precursor manufactured in process (II) comprises lithium aluminosilicate and silicon particles. In process (II), the lithium aluminosilicate and silicon particles are mixed and ground. Specifically, the lithium aluminosilicate and silicon particles are introduced into a container such as a ball mill, and then the lithium aluminosilicate and silicon particles are mixed and ground by rotating the ball mill. Here, the mass ratio of the lithium aluminosilicate and silicon particles is preferably such that the silicon particles are 40 to 90 mass% with respect to the lithium aluminosilicate being 10 to 60 mass%. It is desirable that the mass of the lithium aluminosilicate be within the above range, as this allows for sufficient support of silicon particles included in the negative electrode active material for a lithium-ion secondary battery. Additionally, it is desirable that the mass of the silicon particles be within the above range, as this allows for the maintenance of the cycle characteristics of the lithium-ion secondary battery. In process (II), a precursor of a negative electrode active material for a lithium-ion secondary battery is formed, consisting of a lithium aluminosilicate having a three-dimensional network structure and silicon particles. In process (II), the silicon particles mixed with the lithium aluminosilicate serve as the negative electrode active material for a lithium-ion secondary battery. Furthermore, in process (II), it is desirable that the particle size of the silicon particles included in the mixture of lithium aluminosilicate and silicon particles before mixing and grinding be 0.2 to 100 μm. By setting the particle size of the silicon particles before mixing and grinding to the above range, the particle size of the silicon particles included in the negative electrode active material precursor obtained by mixing and grinding lithium aluminosilicate and silicon particles can be 5 to 100 nm.
[0061] <Process (III); Process of sintering the negative electrode active material precursor under an inert gas atmosphere>
[0062] The method for manufacturing a negative electrode active material for a lithium-ion secondary battery according to the present embodiment comprises: process (III); and a process of sintering the negative electrode active material precursor prepared in process (II) under an inert gas atmosphere. By sintering the negative electrode active material precursor under an inert gas atmosphere, the negative electrode active material precursor becomes a negative electrode active material for a lithium-ion secondary battery. Furthermore, in process (III), in order to control the oxygen non-compatibility δ in the lithium aluminosilicate, which is the main phase of the matrix constituting the negative electrode active material for a lithium-ion secondary battery, sintering may be performed under an oxygen atmosphere before sintering under an inert gas atmosphere. Also, in process (III), in order to control the oxygen non-compatibility δ in the lithium aluminosilicate, which is the main phase of the matrix constituting the negative electrode active material for a lithium-ion secondary battery, sintering may be performed in the presence of a reducing agent before sintering under an inert gas atmosphere. In this way, process (III) can compensate for oxygen defects accompanied by oxygen vacancies and metal defects caused by excess oxygen by sintering the negative electrode active material precursor in an oxygen gas atmosphere or in the presence of a reducing agent as a preliminary process.
[0063] The sintering temperature of the negative electrode active material precursor is preferably 500 to 1000°C. It is preferable that the sintering temperature of the negative electrode active material precursor be 500°C or higher, as the structure of the negative electrode active material for a lithium-ion secondary battery is stabilized by heating the negative electrode active material precursor; it is preferable that the temperature be 1000°C or lower, as decomposition of the negative electrode active material precursor does not occur. The heat treatment time of the negative electrode active material precursor is preferably 0.5 to 40 hours, and particularly preferably 1 to 20 hours. It is preferable that the heat treatment time be 0.5 hours or longer, as the reaction of the precursor proceeds. It is preferable that the heat treatment time be 40 hours or less, as this suppresses the volatilization of Li. In addition, the sintering of the negative electrode active material precursor is carried out in the presence of an inert gas such as nitrogen or argon. This is because the negative electrode active material precursor does not react with oxygen in the atmosphere, the structure of the composite becomes robust, and a stabilized negative electrode active material for a lithium-ion secondary battery can be obtained.
[0064] FIG. 5 is the result of X-ray diffraction (XRD) of a negative electrode active material for a lithium-ion secondary battery, which is a composite of LiAlSiO4 and Si (silicon particles), manufactured via processes (I) to (III) included in the method for manufacturing a negative electrode active material for a lithium-ion secondary battery according to the present embodiment. Specifically, FIG. 5(a) is the result of X-ray diffraction (XRD) of the negative electrode active material for a lithium-ion secondary battery, which is a composite of LiAlSiO4 and Si (silicon particles), manufactured. FIG. 5(b) is the result of X-ray diffraction (XRD) of the Si (silicon particles) included in the negative electrode active material for a lithium-ion secondary battery, which is a composite of LiAlSiO4 and Si (silicon particles), manufactured (Non-patent Literature 1). Figure 5(c) is the result of X-ray diffraction (XRD) of LiAlSiO4 included in a negative electrode active material for a lithium-ion secondary battery, which is a composite of manufactured LiAlSiO4 and Si (silicon particles) (non-patent literature 2).
[0065] As is evident from FIG. 5(a), the composite obtained by mixing lithium aluminosilicate and silicon particles and grinding them by process (III) to sinter the negative electrode active material precursor has peaks at 28.43, 47.29, and 56.11 (2θ / deg) originating from the silicon particles, and peaks at 25.26, 47.56, and 55.96 (2θ / deg) originating from LiAlSiO4.
[0066] It was found that these peaks closely match the diffraction peaks of Si and LiAlSiO4 listed in the database of the National Institute for Materials Science (NIMS) (Atom Work; http: / / crystdb.nims.go.jp / ). From these X-ray diffraction (XRD) measurement results, it was determined that the complex compound produced by the method for manufacturing a negative electrode active material for a lithium-ion secondary battery according to the present embodiment is a complex of LiAlSiO4 and Si (silicon particles).
[0067] As shown in FIG. 5(a), it is evident that the negative electrode active material for a lithium-ion secondary battery, prepared by the method for preparing a negative electrode active material for a lithium-ion secondary battery according to the present embodiment, is a mixture of lithium aluminosilicate and silicon particles, and has a structure in which silicon particles are dispersed in a matrix having a polycrystalline LiAlSiO4 with a three-dimensional network structure.
[0068] The negative electrode active material for a lithium-ion secondary battery, which is a mixture of silicon particles and a matrix having lithium aluminosilicate as the main component, manufactured by the method for manufacturing a negative electrode active material for a lithium-ion secondary battery according to the present embodiment, can maintain its microstructure as a three-dimensional network structure even after charging and discharging a lithium-ion secondary battery equipped with a negative electrode containing the said negative electrode active material. That is, the negative electrode active material for a lithium-ion secondary battery manufactured by the method for manufacturing a negative electrode active material for a lithium-ion secondary battery according to the present embodiment has a technical feature in that, as the lithium aluminosilicate has a three-dimensional network structure, it can maintain the network (three-dimensional network structure) formed three-dimensionally between aluminum (Al), silicon (Si), and oxygen (O), which forms the basis of the microstructure, even after charging and discharging a lithium-ion secondary battery equipped with a negative electrode containing the said negative electrode active material.
[0069] Figure 6 is a graph showing the X-ray diffraction (XRD) measurement results of a composite (after charging and discharging the secondary battery) composed of LiAlSiO4 and Si (silicon particles) constituting the negative electrode active material for a lithium-ion secondary battery according to the present invention. Specifically, Figure 6(a) is the measurement result of X-ray diffraction (XRD) of a negative electrode containing the negative electrode active material for a lithium-ion secondary battery to confirm the form in which the crystals of LiAlSiO4 exist after the secondary battery charge-discharge cycle. In the X-ray diffraction (XRD) of the negative electrode shown in Figure 6(a), in order to exclude the influence of graphite (MAG), an electrode with a ratio of Si negative electrode 91%, binder CMC 3.0%, binder SBR 3.0%, and conductivity aid acetylene black 3.0% was fabricated in the same order as shown in the embodiment of the invention. For X-ray diffraction (XRD) measurement, a cycle test was performed with a charge / discharge current of 0.5 mA, and after 5 cycles, the coin-type secondary battery was disassembled in a glove box and the removed negative electrode was used.
[0070] Figure 6(b) shows the diffraction peaks of LiAlSiO4 listed in the National Institute for Materials Science (NIMS) database (Atom Work ; http: / / crystdb.nims.go.jp / ).
[0071] It has been found that LiAlSiO4, which constitutes the negative electrode active material for a lithium-ion secondary battery shown in Fig. 6(a), has a diffraction line peak of LiAlSiO4 shown in Fig. 6(b) at around 25°. That is, it has been revealed that the negative electrode active material for a lithium-ion secondary battery according to the present embodiment is a crystal that maintains a network (three-dimensional network structure) formed between Al, Si, and O in three dimensions, which forms the basis of its microstructure, even after charging and discharging a lithium-ion secondary battery equipped with a negative electrode containing the negative electrode active material for a lithium-ion secondary battery.
[0072] As explained above, according to the method for manufacturing a negative electrode active material for a lithium-ion secondary battery of the present embodiment, a lithium aluminosilicate having a three-dimensional network structure in which the bonds of aluminum (Al), silicon (Si), and oxygen (O) are formed three-dimensionally is used as a matrix, and a negative electrode active material for a lithium-ion secondary battery can be manufactured in the form of a composite in which silicon particles are dispersed in the matrix even after charging and discharging.
[0073] [Third Embodiment]
[0074] A negative electrode for a lithium-ion secondary battery according to the third embodiment will be described. The negative electrode for a lithium-ion secondary battery according to the present embodiment includes the negative electrode active material for a lithium-ion secondary battery according to the above embodiment. The negative electrode including the negative electrode active material for a lithium-ion secondary battery according to the present embodiment enables doping and dedoping of lithium ions at a lower potential than that of the positive electrode. Examples of the forms of the negative electrode for a lithium-ion secondary battery according to the present embodiment include a negative electrode formed by supporting a negative electrode composite containing the negative electrode active material for a lithium-ion secondary battery according to the above embodiment on a negative electrode current collector, and a negative electrode composed solely of the negative electrode active material for a lithium-ion secondary battery according to the above embodiment.
[0075] (Other negative electrode active materials)
[0076] The negative electrode active material for a lithium-ion secondary battery included in the negative electrode of the present embodiment may include other negative electrode active materials in the negative electrode active material of the lithium-ion secondary battery of the above embodiment to a extent that does not interfere with the purpose of the present invention. Other negative electrode active materials may include carbon materials, oxides, sulfides, nitrides, metals, or alloys, which are materials capable of doping and undoping lithium ions at a potential lower than that of the positive electrode.
[0077] Other carbon materials that can be used as negative electrode active materials include graphite such as natural graphite and artificial graphite, coke, carbon black, pyrolytic carbon, carbon fiber, and sintered organic polymer compounds. Only one of these carbon materials, oxides, sulfides, nitrides, etc. may be used, or two or more may be used in combination. In addition, these carbon materials, oxides, sulfides, nitrides, etc. may be either crystalline or amorphous.
[0078] Among the other negative electrode active materials mentioned above, carbon materials with graphite as the main component, such as natural graphite or synthetic graphite, are preferably used for reasons such as the negative electrode potential remaining almost unchanged from the uncharged state to the fully charged state during charging (good potential flatness), the average discharge potential being low, and the capacity retention rate being high when repeatedly charged and discharged (good cycle characteristics). The shape of the carbon material may be any of the following: flake-like, such as natural graphite; spherical, such as mesocarbon micro beads; fibrous, such as graphitized carbon fibers; or aggregates of fine powder.
[0079] The negative electrode composite may contain a binder as needed. Examples of binders include thermoplastic resins, specifically polyvinylidene fluoride, thermoplastic polyimide, carboxymethylcellulose, polyethylene, and polypropylene.
[0080] (The entire Bu-geuk house)
[0081] As a negative current collector for the negative electrode of the present embodiment, a band-shaped member made of a metal material such as copper (Cu), nickel (Ni), or stainless steel can be used as the forming material. Among these, it is preferable to use copper (Cu) as the forming material and process it into a thin film shape, as it does not easily form an alloy with lithium and is easy to process.
[0082] Methods for supporting a negative electrode composite on such a negative electrode current collector include pressure molding and a method of forming a paste using a solvent, applying it onto the negative electrode current collector, drying it, and then pressing it.
[0083] As explained above, the negative electrode for a lithium-ion secondary battery according to the present embodiment comprises a negative electrode active material for a lithium-ion secondary battery in which silicon particles are dispersed in a matrix containing lithium aluminosilicate having a three-dimensional network structure. Accordingly, a secondary battery equipped with the negative electrode for a lithium-ion secondary battery according to the present embodiment has excellent charge-discharge capacity retention rate (cycle characteristics) and also possesses cycle characteristics that are particularly desirable as a lithium-ion secondary battery for automotive applications.
[0084] [Fourth Embodiment]
[0085] A lithium-ion secondary battery of the fourth embodiment will be described. FIG. 8 is a model diagram showing the structure of a lithium-ion secondary battery equipped with a negative electrode for a lithium-ion secondary battery. As shown in FIG. 8, the lithium-ion secondary battery of the present embodiment is equipped with a negative electrode for a lithium-ion secondary battery of the above embodiment. In addition, regarding the shape of the negative electrode for the lithium-ion secondary battery, for example, a columnar shape in which the cross-sectional shape when the electrode is cut perpendicular to the axis of winding is a circle, an ellipse, a rectangle, or a rectangle with rounded corners can be cited.
[0086] In addition, as a specific example of a lithium-ion secondary battery having such an electrode, the shape of the lithium secondary battery may adopt a shape defined in IEC 60086, a battery standard established by the International Electrotechnical Commission (IEC), or JIS C8500. For example, preferred shapes for the negative electrode of the lithium-ion secondary battery include cylindrical and prismatic shapes. Furthermore, the negative electrode of the lithium-ion secondary battery equipped with the lithium-ion secondary battery is not limited to the above-mentioned wound configuration, but may also have a stacked configuration in which a stacked structure of a positive electrode, a separator, the negative electrode, and a separator is repeatedly superimposed. Examples of stacked lithium secondary batteries include so-called coin-type batteries, button-type batteries, and paper-type (or sheet-type) batteries.
[0087] The lithium-ion secondary battery of the present embodiment comprises, in addition to the negative electrode for the lithium-ion secondary battery of the above embodiment, a positive electrode mainly comprising a positive electrode active material, an electrolyte, and a separator. Each component is described below.
[0088] Positive electrode
[0089] The positive electrode of the lithium-ion secondary battery of the present embodiment can be manufactured by preparing a positive electrode composite containing a positive electrode active material, a conductive material, and a binder, and by supporting the positive electrode composite on a positive electrode current collector.
[0090] (Positive electrode active material)
[0091] As a positive electrode active material, a compound capable of reversible intercalation and deintercalation of lithium (lithiation intercalation compound) may be used. Specifically, one or more composite oxides of lithium and a metal such as cobalt, manganese, nickel, or a combination thereof may be used. Specific examples of the positive electrode active material include lithium cobaltate, lithium nickelate, lithium manganate, etc.
[0092] (Challenge)
[0093] Carbon materials may be used as the conductive material included in the positive electrode of the lithium-ion secondary battery of the present embodiment. Examples of carbon materials include graphite powder, carbon black (e.g., acetylene black), and fibrous carbon materials. Since carbon black is fine and has a large surface area, adding a small amount to the positive electrode composite can increase the conductivity within the positive electrode, thereby improving charge / discharge efficiency and output characteristics. On the other hand, if an excessive amount of carbon black is added, the binding force between the positive electrode composite and the positive electrode current collector by the binder, as well as the binding force within the positive electrode composite, are all reduced, which conversely causes an increase in internal resistance.
[0094] The ratio of the conductive material in the positive electrode composite is preferably 5 to 20 parts by mass per 100 parts by mass of the positive electrode active material. When fibrous carbon materials such as graphitized carbon fibers or carbon nanotubes are used as the conductive material, this ratio can be lowered.
[0095] (bookbinder)
[0096] Thermoplastic resins may be used as binders for the positive electrode. Examples of such thermoplastic resins include fluoropolymers such as polyvinylidene fluoride, polytetrafluoroethylene, tetrafluoroethylene-hexafluoropropylene-vinylidene fluoride copolymers, hexafluoropropylene-vinylidene fluoride copolymers, and tetrafluoroethylene-perfluorovinylether copolymers, as well as polyolefin resins such as polyethylene and polypropylene. Two or more of these thermoplastic resins may be used in combination.
[0097] (The entire drama house)
[0098] As the positive electrode current collector of the present embodiment, a target member made of a metal material such as aluminum (Al), nickel (Ni), or stainless steel can be used. Among these, it is preferable to use aluminum (Al) as the forming material and process it into a thin film shape, as it is easy to process and inexpensive.
[0099] One method for supporting a positive electrode composite on a positive electrode current collector is to press-mold the positive electrode composite onto the positive electrode current collector. Alternatively, the positive electrode composite may be supported on the positive electrode current collector by using an organic solvent to form a paste of the positive electrode composite, applying the resulting paste of the positive electrode composite to at least one side of the positive electrode current collector, drying it, and then pressing it to fix it.
[0100] When forming a positive electrode mixture into a paste, organic solvents that can be used include amine-based solvents such as N,N-dimethylaminopropylamine and diethylenetriamine, ether-based solvents such as tetrahydrofuran, ketone-based solvents such as methyl ethyl ketone, ester-based solvents such as methyl acetate, and amide-based solvents such as dimethylacetamide and N-methyl-2-pyrrolidone.
[0101] Methods for applying a positive electrode paste to a positive electrode current collector include, for example, slit die coating, screen coating, curtain coating, knife coating, gravure coating, and electrostatic spraying.
[0102] Separator
[0103] As a separator for the lithium-ion secondary battery of the present embodiment, for example, a material having the form of a porous membrane, nonwoven fabric, woven fabric, etc., made of a polyolefin resin such as polyethylene or polypropylene, a fluoropolymer, or a nitrogen-containing aromatic polymer, may be used. In addition, a separator may be formed by using two or more of these materials, or by stacking these materials to form a separator.
[0104] In the lithium-ion secondary battery of the present embodiment, the separator preferably has a permeability resistance according to the Gullley method specified in JIS P8117 of 50 sec / 100 cc or more and 300 sec / 100 cc or less in order to allow good permeation of the electrolyte during battery use (charging and discharging), and more preferably 50 sec / 100 cc or more and 200 sec / 100 cc or less.
[0105] Electrolyte
[0106] The electrolyte of the lithium-ion secondary battery of the present embodiment may contain an electrolyte and an organic solvent. The electrolyte contained in the electrolyte may be LiClO4, LiPF6, LiAsF6, LiSbF6, LiBF4, LiCF3SO3, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiN(SO2CF3)(COCF3), Li(C4F9SO3), LiC(SO2CF3)3, Li2B 10 Cl 10 Examples include lithium salts such as LiBOB (where BOB represents bis(oxalato)borate), LiFSI (where FSI represents bis(fluorosulfonyl)imide), lower aliphatic carboxylate lithium salts, and LiAlCl4. Additionally, a mixture of two or more electrolytes selected from these electrolytes may be used. As for the electrolyte, it is preferable to use one selected from the group consisting of fluorine-containing LiPF6, LiAsF6, LiSbF6, LiBF4, LiCF3SO3, LiN(SO2CF3)2, and LiC(SO2CF3)3.
[0107] As organic solvents, carbonates, ethers, nitriles, carbamates, and sulfur-containing compounds may be used. Examples of carbonates include propylene carbonate, ethylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, 4-trifluoromethyl-1,3-dioxolane-2-one, 1,2-di(methoxycarbonyloxy)ethane, etc. Examples of ethers include 1,2-dimethoxyethane, 1,3-dimethoxypropane, pentafluoropropylmethyl ether, 2,2,3,3-tetrafluoropropyldifluoromethyl ether, tetrahydrofuran, 2-methyltetrahydrofuran, etc. Examples of esters include methyl formate, methyl acetate, and γ-butyrolactone. Examples of nitriles include acetonitrile and butyronitrile. Examples of amides include N,N-dimethylformamide and N,N-dimethylacetamide. Examples of carbamates include 3-methyl-2-oxazolidone. Examples of sulfur-containing compounds include sulfolane, dimethyl sulfoxide, 1,3-propanesulfone, etc.
[0108] As for organic solvents, it is preferable to use a mixture of two or more of these. Among them, a mixed solvent containing carbonates is preferred, and a mixed solvent of cyclic carbonates and acyclic carbonates, and a mixed solvent of cyclic carbonates and ethers are even more preferred.
[0109] A solid electrolyte may be used instead of an electrolyte. As a solid electrolyte, organic polymer electrolytes may be used, such as a polymer compound based on polyethylene oxide, a polymer compound containing at least one of a polyorganosiloxane chain or a polyoxyalkylene chain. In addition, a so-called gel type in which a non-aqueous electrolyte is retained in a polymer compound may be used. In addition, inorganic solid electrolytes containing sulfides such as Li2S-SiS2, Li2S-GeS2, Li2S-P2S5, Li2S-B2S3, Li2S-SiS2-Li3PO4, Li2S-SiS2-Li2SO4, and Li2S-GeS2-P2S5 may be used, and a mixture of two or more of these may be used.
[0110] In addition, when a solid electrolyte is used in the lithium-ion secondary battery of the present embodiment, the solid electrolyte may serve as a separator, and in such cases, a separator may not be required.
[0111] The lithium-ion secondary battery of the present embodiment is a secondary battery and can be repeatedly charged and discharged. For this reason, the lithium-ion secondary battery of the present embodiment is preferred, for example, as a battery for automotive use. In particular, the lithium-ion secondary battery of the present embodiment can be preferably used as a battery mounted in an EV (electric vehicle) that drives a motor using electricity from a battery. EVs (electric vehicles) include BEVs (electric vehicles) and HVs (hybrid vehicles) that use only battery electricity. When applying the lithium-ion secondary battery of the present embodiment to an HV (hybrid vehicle), its use is not limited to that of a battery for a hybrid vehicle that supplies power to a motor for driving the vehicle, but may also be applied in a form that supplies power to a starter motor for restarting the engine in a vehicle equipped with an idling stop function. Furthermore, the secondary battery includes the primary battery use of the secondary battery (use intended for a single discharge after charging).
[0112] As explained above, the lithium-ion secondary battery of the present embodiment has a negative electrode containing a negative electrode active material for a lithium-ion secondary battery in which silicon particles are dispersed in a matrix containing a lithium aluminosilicate having a three-dimensional network structure, so it has excellent charge / discharge capacity retention rate (cycle characteristics) and particularly has cycle characteristics desirable as a lithium-ion secondary battery for automotive applications.
[0113] [Other embodiments]
[0114] Although the present invention has been described above with reference to embodiments, the present invention is not limited to the above embodiments. Various modifications that can be understood by those skilled in the art within the technical scope of the present invention may be made to the configuration or details of the present invention.
[0115] Examples
[0116] (Example 1)
[0117] As a matrix for dispersing silicon particles, LiAlSiO4, a lithium aluminosilicate, was prepared by setting x = 1.0, y = 1.0, and δ = 0 in the above general formula (1). After preparing a negative electrode active material for a lithium-ion secondary battery using a matrix having LiAlSiO4 as the main phase, a negative electrode containing said negative electrode active material was prepared. In addition, a coin-type secondary battery, which is a lithium-ion secondary battery equipped with said negative electrode, was prepared. Then, an evaluation (discharge capacity retention rate (cycle characteristics)) of the prepared coin-type secondary battery was performed. Specifically, a negative electrode active material, a negative electrode, and a coin-type secondary battery were prepared as follows, and said coin-type secondary battery was evaluated.
[0118] <Manufacturing of negative electrode active material>
[0119] As raw materials for the matrix included in the negative electrode active material, lithium carbonate (Li2CO3), silicon dioxide (SiO2), and aluminum hydroxide (Al(OH)3) are LiAlSi 0.6 O 3.2 The materials were weighed to have a composition of (in mass %, Li = 38.5%, Si = 23.0%, M(Al) = 38.5%), and these raw materials were fed into a rotary-vibrating powder mixer (locking mixer; "RM10-3" manufactured by Aichi Electric Co., Ltd.) and dry mixing was performed for 4.0 hours. A nylon ball mill (with an iron core inserted and a diameter Φ: 20 mm) was used as the medium for the dry mixing. After the completion of the dry mixing, a mixed powder of lithium carbonate (Li2CO3), silicon dioxide (SiO2), and aluminum hydroxide (Al(OH)3) was obtained. The obtained mixed powder was calcined at 800 to 1000 °C under an atmospheric pressure atmosphere to obtain a matrix having lithium aluminosilicic acid as the main phase.
[0120] The diffraction pattern of the obtained lithium aluminosilicate was measured by X-ray diffraction (XRD), and the XRD profile shown in Fig. 7(a) was obtained. Fig. 7(a) is the measured XRD profile of the lithium aluminosilicate prepared in Example 1. In Fig. 7(b), the diffraction peaks of the known LiAlSiO4 are shown as a reference XRD profile. In addition, the reference XRD profile showing the diffraction peaks of the known LiAlSiO4 shown in Fig. 7(b) represents the diffraction peaks of LiAlSiO4 listed in the National Institute for Materials Science (NIMS) database (Atom Work; http: / / crystdb.nims.go.jp / ).
[0121] When comparing the measured XRD profile of the lithium aluminosilicate prepared in Example 1 shown in Fig. 7(a) with the reference XRD profile showing the diffraction peaks of the known LiAlSiO4 shown in Fig. 7(b), it was confirmed that in the measured XRD profile of the lithium aluminosilicate prepared in Example 1, the reflection peak of the LiAlSiO4 compound exists as a main peak around 25.25 (2θ / deg). Based on this result, it became clear that the main phase of the matrix prepared in Example 1 is a lithium aluminosilicate having a three-dimensional network structure.
[0122] As a raw material for the negative electrode active material, a mixture of a matrix consisting of the obtained LiAlSiO4 and Si (silicon particles) was used. A predetermined amount of LiAlSiO4 and Si (silicon particles) was fed into a planetary ball mill (Classic Line P-5 manufactured by Fritz, Germany) and ground at a rotational speed of 200 rpm for 15.0 hours. For the Si (silicon particles), silicon particles with an average particle size of 10 μm were used. In addition, chrome steel balls (diameter Φ 20 mm) were used as the media for grinding.
[0123] The raw material of the crushed negative electrode active material was heat-treated at a temperature of 500 to 1000 °C for 1 to 100 hours. The sample after heat treatment was crushed by a tungsten mortar and pestle and passed through a sieve with a mesh size of 75 μm, and the sample that fell below the sieve was used as the negative electrode active material. The average particle size of the Si particles contained in the negative electrode active material obtained in this way was 14 nm, calculated by Scherrer's formula based on the full width at half maximum of the diffraction peak attributed to Si (111) centered around 2θ = 28.4° in X-ray diffraction by Cu-Kα rays. In addition, the content of Li and Al in the negative electrode active material was analyzed using an ICP emission spectroscopic analyzer (product name "SPS3520UV-DD" manufactured by Hitachi High-Tech Science Co., Ltd.), and the molar ratio of Li to Al was 1:1.
[0124] A negative electrode slurry was prepared using the obtained negative electrode active material. The negative electrode slurry consists of a negative electrode slurry raw material (negative electrode active material, graphite), a binder CMC, and a binder SBR. The powder of the negative electrode slurry raw material and the powder of the binder CMC are weighed so that the powder of the negative electrode slurry raw material and the powder of the binder CMC included in the negative electrode slurry are in a predetermined mass ratio. Here, the negative electrode slurry raw material consists of 30 mass% of the negative electrode active material and 70 mass% of graphite. Ion-exchanged water was added to the weighed powder of the slurry raw material for the negative electrode and the powder of the binder CMC, and mixing was performed by setting the rotation speed to 2000 rpm and the stirring time to 1.0 hour using a rotating or orbiting mixer (product name "Awatori Rentaro ARE-310" manufactured by THINKY Co., Ltd.) and stirring.
[0125] After mixing, the powder of the raw material for the negative electrode slurry, the powder of the binder CMC, and the liquid containing the ion-exchanged water were mixed, and the viscosity was adjusted by adding dropwise ion-exchanged water. Then, binder SBR was added so that the binder SBR contained in the negative electrode slurry was in a predetermined mass ratio, and mixing was performed by setting the rotation speed to 2000 rpm and the stirring time to 1.0 hour and stirring, thereby obtaining a negative electrode slurry (negative electrode coating slurry). After coating this negative electrode slurry onto a copper (Cu) foil, the negative electrode was manufactured by drying at a drying temperature of 60°C and rolling with a roll mill.
[0126] Manufacture of Coin-Type Secondary Batteries
[0127] As an example of a lithium-ion secondary battery shown in Fig. 8, a coin-type secondary battery was manufactured as follows. A negative electrode was stamped into a circular shape with a diameter Φ: 13 mm, and vacuum drying was performed by setting the drying temperature to 90 ℃ and the drying time to 15.0 h. After vacuum drying, the circular negative electrode was placed into a glove box. Inside the glove box, a coin-type secondary battery was assembled using a component for a CR2032 coin-type secondary battery, metal Li for the counter electrode (lithium; diameter Φ: 15 mm), and a LiPF6 electrolyte with a concentration of 1.0 mol / L (electrolyte LiPF6, electrolyte (ethylene carbonate (EC): diethyl carbonate (DEC)).
[0128] Evaluation of Coin-type Secondary Batteries
[0129] The coin-type secondary battery manufactured above was set in a charge-discharge device, and a CC charge-discharge, 0.0 to 1.0 V, rate 0.1 C (0.5 mA) charge-discharge test was performed. The performance of the negative electrode active material was evaluated by evaluating the discharge capacity retention rate (cycle characteristics) of the coin-type secondary battery. Table 1 and Figure 10 show the measurement results of the discharge capacity retention rate (cycle characteristics) with respect to the number of discharge cycles of a coin-type secondary battery equipped with a negative electrode material containing the negative electrode active material manufactured in Example 1.
[0130] (Example 2)
[0131] A negative electrode active material for a lithium-ion secondary battery was prepared in the same manner as in Example 1, except that by changing the ratio of lithium carbonate (Li2CO3), silicon dioxide (SiO2), and aluminum hydroxide (Al(OH)3) included in the raw materials of the matrix included in the negative electrode active material, LiAlSi2O6 (Example 2) was prepared in which x = 1.0, y = 2.0, and δ = 0 in the above general formula (1) representing lithium aluminosilicate as a matrix for dispersing silicon particles. In addition, a negative electrode containing the said negative electrode active material was prepared, and a coin-type secondary battery, which is a lithium-ion secondary battery equipped with the said negative electrode, was prepared, and the discharge capacity retention rate (cycle characteristics) of the coin-type secondary battery was evaluated in the same manner as in Example 1. Table 1 shows the measurement results of the discharge capacity retention rate (cycle characteristics) with respect to the number of discharge cycles of a coin-type secondary battery equipped with a negative electrode material including the negative electrode active material prepared in Example 2.
[0132] (Comparative Example 1)
[0133] As raw materials for the matrix included in the negative electrode active material, lithium carbonate (Li2CO3), silicon dioxide (SiO2), and aluminum hydroxide (Al(OH)3) are LiAlSi 0.1 O 2.65A negative electrode active material for a lithium-ion secondary battery was prepared in the same manner as in Example 1, except that a matrix was prepared by dispersing silicon particles by weighing the materials to have a composition of (in mass %, Li = 47.6%, Si = 47.6%, M(Al) = 4.8%). The diffraction pattern of the obtained matrix was measured by X-ray diffraction (XRD), and the XRD profile shown in Fig. 9(a) was obtained. Fig. 9(a) is the measured XRD profile of the matrix prepared in Comparative Example 1. In addition, the diffraction peaks of known Li2Si2O5 are shown in Fig. 9(b) as a reference XRD profile. Fig. 9(b) shows the diffraction peaks of Li2Si2O5 listed in the International Centre for Diffraction Data (ICDD) database.
[0134] When the measured XRD profile of the matrix prepared in Comparative Example 1 shown in Fig. 9(a) is examined in detail in comparison with the diffraction peak of the known Li2Si2O5 shown in Fig. 9(b) and the reference XRD profile, it was confirmed that the reflection peak of the Li2Si2O5 compound exists as the main peak in the measured XRD profile of the matrix prepared in Comparative Example 1. Based on this result, it became clear that the main phase of the matrix prepared in Comparative Example 1 is lithium silicate (two-dimensional layered structure).
[0135] In addition, a negative electrode containing the said negative electrode active material was manufactured, and a coin-type secondary battery, which is a lithium-ion secondary battery equipped with the said negative electrode, was manufactured. For this coin-type secondary battery, the discharge capacity retention rate (cycle characteristics) of the coin-type secondary battery was evaluated in the same manner as in Example 1. Table 1 and Figure 10 show the measurement results of the discharge capacity retention rate (cycle characteristics) with respect to the number of discharge cycles of a coin-type secondary battery equipped with a negative electrode material containing the negative electrode active material manufactured in Comparative Example 1.
[0136]
[0137] (Evaluation Results)
[0138] The discharge capacity retention rate (cycle characteristics) of a secondary battery equipped with a negative electrode containing the negative electrode active material prepared in Examples 1 and 2 was compared with the discharge capacity retention rate (cycle characteristics) of a secondary battery prepared in Comparative Example 1. As is evident from Table 1, the discharge capacity retention rate (cycle count 16) of the secondary battery equipped with the negative electrode containing the negative electrode active material prepared in Examples 1 and 2 was 77%, whereas the discharge capacity retention rate of Comparative Example 1 at the same cycle count was 66%, which is significantly different. This trend is more pronounced at cycle count 25. Figure 10 shows the change in discharge capacity retention rate accompanying this cycle count in more detail. From this figure as well, it can be confirmed that the discharge capacity retention rate according to the examples always exceeds that of the Comparative Example, and that this difference becomes more pronounced with an increase in the number of charge-discharge cycles. From these evaluation results, it became clear that a secondary battery equipped with a negative electrode containing the negative electrode active material of the present invention exhibits a good discharge capacity retention rate (cycle characteristics).
[0139] As such, the basic effect expected from the lithium aluminosilicate having a three-dimensional network structure included in the negative electrode active material for a lithium-ion secondary battery related to the present invention is the improvement of the discharge capacity retention rate (cycle characteristics) of a secondary battery equipped with a negative electrode containing the negative electrode active material for a lithium-ion secondary battery. That is, the basic effect exhibited by the negative electrode active material for a lithium-ion secondary battery related to the present invention is considered to be the same whether the electrolyte of the lithium-ion secondary battery is a non-aqueous electrolyte or a solid electrolyte.
[0140] When the electrolyte of a lithium-ion secondary battery is an electrolyte-based (non-aqueous electrolyte), the expansion and contraction of silicon particles (Si particles) are suppressed by the effect exhibited by the lithium aluminosilicate having a three-dimensional network structure included in the negative electrode active material for the lithium-ion secondary battery. As a result, the disintegration of silicon particles (Si particles) included in the negative electrode active material for the lithium-ion secondary battery—that is, the detachment of silicon particles (Si particles) from the negative electrode of the lithium-ion secondary battery—or the deactivation of silicon particles (Si particles) caused by the electrolyte reacting with the silicon particles (Si particles) can be prevented. Thus, when a negative electrode containing the negative electrode active material for a lithium-ion secondary battery related to the present invention is provided and the electrolyte is an electrolyte-based (non-aqueous electrolyte), the lifespan characteristics of the secondary battery are improved.
[0141] Meanwhile, when the electrolyte of a lithium-ion secondary battery is a solid electrolyte, the expansion and contraction of silicon particles (Si particles) are suppressed by the effect of the lithium aluminosilicate having a three-dimensional network structure included in the negative electrode active material for the lithium-ion secondary battery. As a result, the solid electrolyte and the negative electrode active material for the lithium-ion secondary battery, which is a composite in which silicon particles are dispersed in a matrix containing lithium aluminosilicate having a three-dimensional network structure, are more likely to maintain a state of close contact, thereby improving the lifespan characteristics of the secondary battery. Furthermore, by adopting a solid electrolyte as the electrolyte for the lithium-ion secondary battery, it becomes possible to make the lithium-ion secondary battery all solid. As a result, the safety and reliability of the lithium-ion secondary battery are dramatically improved, and it becomes possible to increase energy density and power output.
[0142] Industrial applicability
[0143] The negative electrode active material for a lithium-ion secondary battery according to the present invention exhibits excellent discharge capacity, cycle life characteristics, and high-rate discharge characteristics. For this reason, it is not only desirable as a negative electrode material for alkaline batteries used in hybrid vehicles or idling stop vehicles, but can also be preferably used in alkaline batteries for electric vehicles, making it industrially useful in the electrical industry, automotive industry, and the like. Explanation of the symbols
[0144] 100 : Coin-type secondary battery 101 : Top lid 111 : Straight Drama 112 : Spacer 113 : SUS spring 114 : Glass filter 102 : Sauce 121 : Bu-geuk 122 : Packing 103 : Electrolyte 104 : Separator
Claims
Claim 1 A negative electrode active material for a lithium-ion secondary battery, characterized in that silicon particles are dispersed in a matrix having a lithium aluminosilicate having a three-dimensional network structure, wherein the lithium aluminosilicate is represented by the following general formula (1), and in general formula (1), the ratio (y / x) of Si to Al is in the range of 1.0 ≤ (y / x) ≤ 5.
5. Here, in the above general formula (1), x satisfies the conditions 0.4 ≤ x ≤ 2.5, y 0.4 ≤ y ≤ 6.8, and δ -0.4 ≤ δ ≤ 0.
4. Claim 2 delete Claim 3 A negative electrode active material for a lithium-ion secondary battery according to claim 1, characterized in that the lithium aluminosilicate is at least one selected from LiAlSiO4, LiAlSi2O6, and LiAlSi3O8. Claim 4 A negative electrode active material for a lithium-ion secondary battery according to claim 1, wherein the lithium aluminosilicate has, in the crystal structure analysis by X-ray diffraction method specified in JIS H7805:2005, diffraction peaks 2θ (deg) originating from silicon of 28.20 to 28.60, 47.10 to 47.50, and 55.90 to 56.30, and diffraction peaks 2θ (deg) originating from the lithium aluminosilicate of 25.10 to 25.90, 47.10 to 47.90, and 55.80 to 56.
80. Claim 5 A negative electrode active material for a lithium-ion secondary battery according to claim 1, characterized in that the content of the silicon particles included in the negative electrode active material for a lithium-ion secondary battery is 40 to 90 mass%. Claim 6 A negative electrode active material for a lithium-ion secondary battery, characterized in that, in claim 1, the average particle size of the silicon particles is 5 to 100 nm. Claim 7 A method for manufacturing a negative electrode active material for a lithium-ion secondary battery in which silicon particles are dispersed in a matrix containing lithium aluminosilicate, comprising: process (I); a process of manufacturing lithium aluminosilicate having a three-dimensional network structure by mixing and grinding lithium carbonate, aluminum hydroxide, and silicon dioxide, and then calcining at a temperature of 800 to 1000 °C under an atmospheric pressure atmosphere; process (II); a process of manufacturing a negative electrode active material precursor by mixing and grinding the lithium aluminosilicate manufactured in process (I) and silicon particles; and process (III). A method for manufacturing a negative electrode active material for a lithium-ion secondary battery, comprising a process of sintering the negative electrode active material precursor manufactured in the above process (II) under an inert gas atmosphere, wherein the lithium aluminosilicate is represented by the following general formula (1), and wherein the ratio (y / x) of Si to Al in the general formula (1) is in the range of 1.0 ≤ (y / x) ≤ 5.
5. Here, in the above general formula (1), x satisfies the conditions 0.4 ≤ x ≤ 2.5, y 0.4 ≤ y ≤ 6.8, and δ -0.4 ≤ δ ≤ 0.
4. Claim 8 A negative electrode for a lithium-ion secondary battery characterized by comprising a negative electrode active material for a lithium-ion secondary battery as described in any one of claims 1 and 3 to 6.
Citation Information
Patent Citations
Negative electrode active material for non-aqueous electrolyte secondary batteries
US20200350563A1